Factors Affecting the Decision to Choose the Farmland Model in Le Tri Commune, Tri Ton District, An Giang Province, Vietnam - Y Thi Le; Hieu Van Tran (International Journal of Agricultural Sciences, 2019)
The study evaluated factors affecting the selection of agricultural farming models and advantages, difficulties, and opportunities in the implementation process to propose solutions to develop appropriate agricultural sustainable farming models. The study uses secondary and primary data through KIP interviews, focus group interviews, in-depth interviews, and farmer interviews. As a result, this study found education is an important factor affecting farmers in choosing their farming models and increasing agricultural production in their farmland. For most of the considered factors, the majority of Kinh people choose to evaluate the influence of the decision in choosing a farming model higher than another ethnic group (Khmer). Besides, the Khmer ethnic group accounts for a higher proportion of poor households (18.2%) than the Kinh group. Because of low economic conditions, decisions on agricultural production of Khmer ethnic groups are less assertive than that of the Kinh people. On the other hand, there is a serious shortage of water in the dry season in the highlands, cultivated mainly by rainwater, ethnic minority accounts for 53.36% of the whole commune population, educational level makes it difficult to apply modern techniques in production. Therefore, strengthening and mobilizing people, investing in building upland irrigation systems, and using effective land conversion are essential activities to be carried out to improve the efficiency of farming models to make sustainable agricultural production that can increase income and enhance the economic life of local people.